PENGARUH PENGGUNAAN PERBEDAAN KONSTRUKSI MATA PANCING DAN JENIS UMPAN PADA PANCING ULUR TERHADAP HASIL TANGKAPAN DI KAWASAN ZONA PEMANFAATAN PERIKANAN TRADISIONAL TAMAN NASIONAL KARIMUNJAWA - Adityarini, Saraswati; -, Asriyanto; Wibowo, Pramono (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The purpose of this research is to determine the effect of the use of construction of the originally hook with the hook kirbed 30o angle, and the influence of different types of bait is natural bait of meat squid (Loligo sp.) with artificial bait, as well as for determining whether or not the effect of interaction between the form of construction the hook and type of the bait on the catch of hand line in the Traditional Fisheries Utilization Zone of Karimunjawa National Park. The research was conducted in May-April 2012 at the Traditional Fisheries Utilization Zone of Karimunjawa National Park. The material used in this study were the hook used to use squid bait, the hook used to use artificial bait, hook angle of 30 â° with experimental fishing methods. Six times the number of repeat tests. Methods of data analysis begins by looking for the hook rate, the data was processed using a statistical test with SPSS 17 software at 95% level tests with tests of normality, homogeneity test, and two way ANOVA test. The results showed that different types of bait is not so affect the catch, the hook construction differences affect the catch Hand line and interaction between the bait the hook with the use of different constructs had no effect on the catch Hand line. Species of fish caught by fishing gear hand line overall during the study based on the percentage of the amount (kg), namely: Badong, pompano slim, large splotch trevally, pompano gargahing, but there were also fish the sergeant fish Badong fish were the most species of fish caught during the research that is equal to 64% of the 54 tail of the total catch.